Antimicrobial properties of CuO nanorods and multi-armed nanoparticles against B. anthracis vegetative cells and endospores - Pandey, Pratibha; Packiyaraj, Merwyn S.; Nigam, Himangini; Agarwal, Gauri S.; Singh, Beer; Patra, Manoj K. (Beilstein Journal of Nanotechnology, 2014)
Two different kinds of CuO nanoparticles (NPs) namely CuO nanorods (PS2) and multi-armed nanoparticles (P5) were synthesized by wet and electrochemical routes, respectively. Their structure, morphology, size and compositions were characterized by SEM, EDX and XRD. The NPs demonstrated strong bactericidal potential against Bacillus anthracis cells and endospores. PS2 killed 92.17% of 4.5 × 104 CFU/mL B. anthracis cells within 1 h at a dose of 1 mg/mL. Whereas P5 showed a higher efficacy by killing 99.92% of 7 × 105 CFU/mL B. anthracis cells within 30 min at a dose of 0.5 mg/mL and 99.6% of 1.25 × 104 CFU/mL B. anthracis cells within 5 min at a dose of 2 mg/mL. More than 99% of spores were killed within 8 h with 2 mg/mL PS2 in LB media.
Keywords: Bacillus anthracis; bactericidal nanoparticles; copper oxide; nanoparticles; spore inactivation